Use of Antegrade Continence Enema for the Treatment of Fecal Incontinence and Functional Constipation in Adults. Issue 10 (October 2015) - Patel, Abhilasha S.; Saratzis, Athanasios; Arasaradnam, Ramesh; Harmston, Christopher
<x xml:space="preserve">Abstract</x> BACKGROUND: Antegrade continence enema is a proximal colonic stoma that allows antegrade lavage of the colon for the treatment of fecal incontinence and functional constipation. Its role in the treatment of these conditions in adults has not been established. OBJECTIVE: This review aimed to evaluate the clinical response and complications of antegrade continence enema in the adult population. DATA SOURCES: A systematic literature search of MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials databases from January 1980 to October 2013 was conducted. STUDY SELECTION: Studies reporting clinical outcomes of antegrade continence enema in adult patients were considered. Only studies with participants aged 16 years and older were selected. INTERVENTION(S): Use of the antegrade continence enema for the treatment of constipation and incontinence in adults was investigated. MAIN OUTCOME MEASURES: The primary outcome was the number of patients irrigating their stoma. Secondary outcomes included the incidence of stoma stenosis, assessment of functional outcome, and evaluation of quality of life. RESULTS: Overall, 15 studies were selected, describing outcomes in 374 patients. All of the reports were observational cross-sectional studies, and 4 were prospective. The number of participants still using their stoma ranged from 47% to 100% over a follow-up period of 6 to 55 months. Eleven studies reported achievement of full continence in 33% to 100% of patients. Four studies described functional outcomes, and 7 studies reported a wide range of patient satisfaction. The rate of stoma stenosis varied from 8% to 50%. LIMITATIONS: There were considerable heterogeneities within and across studies. Most studies were of poor quality, as reflected in the Methodological Index for Nonrandomized Studies score. CONCLUSIONS: Antegrade continence enema has been reported as an acceptable treatment of both functional constipation and fecal incontinence in adults across several analyses. There is wide variation regarding outcome measures. Larger prospective studies are required to assess the role of antegrade continence enema in the adult population.